Understanding the internationalization process of Havaianas: the important role of brand - Silva, Susana Costa e (2014)
In today’s economy intangible assets account for a large amount of the value created by fi rms. A brand is one of those intangible assets crucial to the attraction of customers and for the creation of emotional bonds with them. Nevertheless, many organisations keep focusing on products and services with often limited functional and technical characteristics, which do not really add value. This paper intends to show how it is possible to reverse this kind of situation: adding value through the creation of a strong brand, and using it to leverage a fi rm’s value, whether national or internationally. With a case study carried out with the sandals business São Paulo Alpargatas, we intend to understand the factors that made its Havaianas brand one of the biggest Brazilian icons abroad. The communication strategy used, the new position achieved with the brand, and the implementation of a long-lasting strategy was some issues we studied, along with Havaianas’ internationalisation process. As a result, we were able to fi nd that the brand’s repositioning was crucial to the successful internationalisation process of the firm.